TAUHIDIC PARADIGM SEBAGAI BASIS DALAM MEWUJUDKAN UMAT BERAGAMA YANG TOLERAN DAN MODERAT - Nuzul Fitriansyah; Rachma Vina Tsurayya (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
The issue of religion and tolerance is always interesting to discuss if we know that someone should be more religious, then more tolerant of his attitude towards others. However, various facts that have occurred in the past few decades indicate that the average cases of intolerance are caused by some individuals who misunderstand the concept of religion even to monopolize a truth. The existence of these facts does not mean making religion a scapegoat that can make a person intolerant, more precisely this happens because of the misunderstanding when someone understands some of the concepts that exist in religion itself. One concept that is the core of any religion is the concept of divinity. In Islam the concept of divinity is known as Tawheed which teaches to disperse God. Some muffasir who take focus in the domain of Liberation Interpretation usually use this monotheistic paradigm as the basis of liberation, say for example Amina Wadud with the issue of rejection of patriarchal culture or Farid Essack who uses this paradigm in eradicating apartheid (discrimination against blacks) that occurs in Africa . Therefore in this case the author tries to offer the use of this monotheistic paradigm to minimize the level of intolerance that occurs due to the existence of miss understanding in understanding religious concepts, where the monotheistic paradigm directs that the true human dignity is the same in the eyes of God so that such views are expected can suppress intolerance and monopoly on truth in the name of religion.